Idea response and adoption in open innovation communities: the signalling role of linguistic style. (6th May 2022) - Hu, Suya; Xu, Di; Wang, Alan
Open innovation communities have become a new trend for organisations to gain external ideas and foster user innovation. However, mass user generated content is making idea selection a tricky and time-consuming work. From the perspective of linguistic styles, this article explores the effects of writing style cues in the content of ideas on idea response and adoption. Our research model is validated through logistic regression on a secondary dataset of 1, 579 ideas collected from the Fantasy Westward Journey Online forum. The results demonstrate that a member's use of self-interest oriented, cognitive oriented and future oriented writing styles has a positive effect on idea response; negative emotionality and cognitive oriented writing styles signal more possibility of idea adoption. We highlight both theoretical implications and managerial applications in innovation management domains.